Semiotics of “Top Gun: Maverick” Film as an Inspiration for Indonesia to Rise up from the Covid-19 Pandemic - Ririt Yuniar; Diah Fitria Ningrum; Imania Rahmah; Ainun N. S. I. P. Sy Saad (Institut Seni Indonesia Yogyakarta, 2023)
Leadership, integrity, and dedication can be a foundation in teamwork. Even integrity is very much needed to achieve a bigger vision and mission to defeat a common enemy. It takes a corps spirit or a sharing the same fate so that the chemistry in a work team becomes more solid. Semiotic analysis of the film Top Gun: Maverick can be appointed as a communicative art study to convey filmmakers’ messages to audiences. Qualitative methods with a construction representation perspective emphasize semiotics and discourse approaches more. The film Top Gun: Maverick as the object material is analyzed in a structured manner from the characterizations, film scenario, or story content in the scene, soundtrack, and cinematography. Cinematography in the film has its definition as a layered meaning. This presents the relationship between the visual signs in the film so that it can create a multi-layer entity. The construction of leadership values and moral messages here illustrates the importance of the spirit of war against a common enemy, shown from various places that can inspire efforts to recover conditions who are also struggling to face a common enemy in the era of the Covid 19 pandemic. During the Covid 19 pandemic, the common enemy took the form of the Coronavirus. which is also a threat to the entire nation and society. This requires an effective and efficient handling strategy. This film continues to inspire the creation of further works to make films the frontline in changing mindsets as an effort to develop human resources as viewers. It is hoped that Indonesian cinema will be able to use leadership strategies as a fundamental factor in realizing the efforts of individuals who have integrity. Semiotika Film TOP GUN: Maverick sebagai Inspirasi Indonesia Bangkit dari Pandemi Covid-19. Kepemimpinan, integritas, dan dedikasi dapat menjadi landasan dalam kerja sama tim. Bahkan integritas sangat dibutuhkan untuk mencapai visi dan misi yang lebih besar untuk mengalahkan musuh bersama. Dibutuhkan corps spirit atau berbagi nasib yang sama agar chemistry dalam sebuah tim kerja semakin solid. Analisis semiotika film Top Gun: Maverick dapat diangkat sebagai kajian seni komunikatif untuk menyampaikan pesan pembuat film kepada penonton. Metode kualitatif dengan perspektif representasi konstruksi lebih menekankan pendekatan semiotika dan wacana. Film Top Gun: Maverick sebagai bahan objek dianalisis secara terstruktur mulai dari penokohan, skenario film, atau isi cerita dalam adegan, soundtrack, dan sinematografi. Sinematografi dalam film memiliki pengertian yang berlapis-lapis. Hal ini menghadirkan hubungan antara tanda-tanda visual dalam film sehingga dapat menciptakan entitas yang berlapis-lapis. Konstruksi nilai kepemimpinan dan pesan moral di sini menggambarkan pentingnya semangat perang melawan musuh bersama, terlihat dari berbagai tempat yang dapat menginspirasi upaya pemulihan kondisi yang juga sedang berjuang menghadapi musuh bersama di era pandemi Covid-19. Selama pandemi Covid-19, musuh bersama berupa virus corona. yang juga merupakan ancaman bagi seluruh bangsa dan masyarakat. Hal ini membutuhkan strategi penanganan yang efektif dan efisien. Film ini terus menginspirasi penciptaan karya-karya selanjutnya untuk menjadikan film sebagai garda terdepan dalam mengubah pola pikir sebagai upaya mengembangkan sumber daya manusia sebagai penonton. Sinema Indonesia diharapkan mampu menggunakan strategi kepemimpinan sebagai faktor fundamental dalam mewujudkan upaya individu yang berintegritas.